Regional Development along the Former Inner-German Border after Unification - Dr. Rupert Kawka (European Regional Science Association (ERSA), 2003)
Borders, border regions and the flows of economically important in- and outputs between two different geographic areas have always been a major subject being studied by regional scientists and geographers. With regard to the eastern enlargement of the EU in the near future, this topic has again gained ground in contemporary Europe. As border regions are mainly peripheral ones, they have the chance to improve their economic situation, as - through the process of integrating different countries - they will be located more in the centre of the new macro region. Nevertheless, there are also fears about negative effects, especially when the economic situations are very different on both sides of the border. A priori, it is not easy to predict whether the positive impact will overweight the negative effect or vice versa. The above described setting applies to the regions along the present eastern EU border. This situation, i.e. the increasing possibilities of interaction between neighbouring regions with a very different economic background (and especially a discrepancy in wealth) is not that new: a comparative case happened in 1990 after the German reunification. Nevertheless, this example is hardly taken as a reference for the future regional development of the frontier regions in eastern Europe. Until 1989, the inner-German border prohibited any interaction between the regions on the western and eastern side of the iron curtain. Quasi over night, migration, commuting and the flow of capital became possible. Furthermore, the regions along both sides of the border were not any longer located in the periphery, they were pushed in a central position in Germany. But on the micro scale, most of these regions are still rather rural areas, and some suffer from the phenomenon called aspatial peripherality. The paper aims at studying all 44 regions (Kreise and kreisfreie Städte) along both the western and the eastern side of the former inner-German border. A first, already published analysis from our own research in the East German State of Sachsen-Anhalt has shown that the former frontier regions have a better economic performance than the whole State. A second example, i.e. the southern part of the State of Thüringen, approves the results. Contrary to these findings, most regions at the western side of the former inner-German border have lower growth rates than the West German average. Nevertheless, some of them serve as ?motors' for the economic development in East Germany. Therefore, the question arises whether the economic development in the regions east of the former inner-German border is determined by West German regions or whether is it possible to speak of an endogenous East German development.
Keywords: 330